Understanding contemporary air power - Fedorchak, Viktoriya (Routledge, 2020)
This textbook aims to explain air power to both military and civilian audiences in an accessible manner, approaching the topic in a balanced and systematic way. The past 100 years illustrates that air power is an inevitable feature of any type of modern warfare. It has a key role to play in any of the three main operational environments: conventional (interstate) wars, peace-support operations and counterinsurgencies. This book examines the strengths and challenges of using air power in these situations, and each type of operation is explained using modern and historical examples, with an emphasis on the relevant lessons for the contemporary and future use of air power. The book also looks into the complexity of media coverage of air warfare and changes in the public perception of air power in recent years. The specifics of structuring national air forces is also discussed, along with the future of air power based on current trends. One of the enduring themes in the book is the necessity of inter-service and cross-domain integration, emphasising the increasingly important role of cyber and space domains in the future of network-centric warfare. This book will be essential reading for students of air power and air warfare, and recommended reading for students of international security, strategic studies, defence studies and foreign policy.